Quantitative imaging of volcanic SO2 plumes using Fabry-Pérot interferometer correlation spectroscopy - Fuchs, Christopher; Kuhn, Jonas; Bobrowski, Nicole; Platt, Ulrich (Atmospheric measurement techniques, 2021)
Abstract. We present first measurements with a novel imaging technique for atmospheric trace gases in the UV spectral range. Imaging Fabry-Pérot interferometer correlation spectroscopy (IFPICS) employs a Fabry-Pérot interferometer (FPI) as the wavelength-selective element. Matching the FPI's distinct, periodic transmission features to the characteristic differential absorption structures of the investigated trace gas allows us to measure differential atmospheric column density (CD) distributions of numerous trace gases with high spatial and temporal resolution. Here we demonstrate measurements of sulfur dioxide (SO2), while earlier model calculations show that bromine monoxide (BrO) and nitrogen dioxide (NO2) are also possible. The high specificity in the spectral detection of IFPICS minimises cross-interferences to other trace gases and aerosol extinction, allowing precise determination of gas fluxes. Furthermore, the instrument response can be modelled using absorption cross sections and a solar atlas spectrum from the literature, thereby avoiding additional calibration procedures, e.g. using gas cells. In a field campaign, we recorded the temporal CD evolution of SO2 in the volcanic plume of Mt. Etna, with an exposure time of 1 s and 400×400 pixel spatial resolution. The temporal resolution of the time series was limited by the available non-ideal prototype hardware to about 5.5 s. Nevertheless, a detection limit of 2.1×1017 molec cm−2 could be reached, which is comparable to traditional and much less selective volcanic SO2 imaging techniques.